Description of symptom course in a telemedicine monitoring clinic for acute symptomatic COVID-19: a retrospective cohort study - James B O'Keefe; Elizabeth J Tong; Ghazala D O'Keefe; David C Tong (BMJ Open, 2021)
Objective Describe the disease course in a cohort of outpatients with COVID-19 and evaluate factors predicting duration of symptoms.Design Retrospective cohort study.Setting Telemedicine clinic at a large medical system in Atlanta, Georgia.Participants 337 patients with acute COVID-19. Exclusion criteria included intake visit more than 10 days after symptom onset and hospitalisation prior to intake visit.Main outcome measures Symptom duration in days.Results Common symptoms at intake visit are upper respiratory (73% cough, 55% loss of smell or taste, 57% sinus congestion, 32% sore throat) and systemic (66% headache, 64% body aches, 53% chills, 30% dizziness, 36% fever). Day of symptom onset was earliest for systemic and upper respiratory symptoms (median onset day 1 for both), followed by lower respiratory symptoms (day 3, 95% CI 2 to 4), with later onset of gastrointestinal symptoms (day 4, 95% CI 3 to 5), when present. Cough had the longest duration when present with median 17 days (95% CI 15 to 21), with 42% not resolved at final visit. Loss of smell or taste had the second longest duration with 14 days (95% CI 12 to 17), with 38% not resolved at final visit. Initial symptom severity is a significant predictor of symptom duration (p<0.01 for multiple symptoms).Conclusions COVID-19 illness in outpatients follows a pattern of progression from systemic symptoms to lower respiratory symptoms and persistent symptoms are common across categories. Initial symptom severity is a significant predictor of disease duration for most considered symptoms.